Effect of prototypicality and dual route processing modal on instructed second language acquisition of Chinese resultative verb compounds - Yafeng, Zhang; Ambigapathy, Pandian; Soo, Ruey Shing (De Gruyter, 2023)
: The present study investigates the processing of Chinese Resultative Verb Compounds (RVCs) in second language (L2) learners. It focuses on the role of prototypicality of component morphemes and whole-word token frequency in L2 acquisition of Chinese RVCs in a formal instructional setting. Chinese RVC is an important linguistic item in Chinese as second or foreign language (CSL/CFL). Cognitive psychology and other areas of research have found that both components of compound and whole word have effect on compound identification. Based on these findings, Pollatsek and his fellows (2000) proposed dual route processing modal (DRPM) which claimed that both the frequency of components and whole-word frequency have effect on compound identification. However, as regards the frequency effect, more empirical evidences showed that prototypicality is a better indicator than frequency in predicting the acquisition of compound. This study aims to explore the effect of formal instruction, prototypicality of components and whole word frequency on RVC identification. By adopting Zhang. (2023. [Forthcoming] Morphological prototypicality of Chinese verb compound and components. Chinese Journal of Applied Linguistics)’s hierarchy of prototypical V1s and RCs, forty two students in two intact classes from Malaysia secondary school participate in a prestest-intervention-posttest research. According to finding in the quasi-experiment study, prototype-based DRPM is proposed with the pedagogical implications that might be conducive to the area of CSL/CFL learning.